Variação Morfológica e Parasitismo em Cnemidophorus ocellifer (Sauria: Teiidae) de áreas de restinga da Ilha do Maranhão, Brasil. - LOPES, Gildevan Nolasco (2009)
This study compared the morphological variation among different populations of Cnemidophorus ocellifer in areas of restinga, and investigated the pattern of sexual dimorphism for this species in this region. Therefore, 130 specimens were collected from four independent areas of restinga in Maranhão Island (Panaquatira, Raposa, Araçagy, and São Marcos Beaches), and measured in the laboratory. Significant morphological differences occurred both for populations and sexes. The populations differed in both body size and shape. The lizards from Raposa showed larger sizes. And the lizards from Panaquatira had more morphological variation, showing shorter limbs and longer trunks. The males of C. ocellifer showed larger body and head, while females had more elongation of the body. The morphological differences were attributed to ecological processes suffered by different groups.